STRATEGI PENGEMBANGAN MOTORIK HALUS ANAK USIA DINI DI TK PGRI AN-NAHL - Aeni Latifah; Siti Aimah; Dewi Untari; Neneng Hadianti; Neng Iqda Abqory (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Fine motor skills in early childhood play a crucial role as a foundational basis for stimulating children’s writing abilities, which are essential for subsequent levels of education. The optimization of these skills can be effectively facilitated through various structured and meaningful activities, such as coloring, cutting, paper folding, and early writing exercises. This article aims to examine the strategies employed in developing fine motor skills among early childhood learners at TK PGRI An-Nahl. The study adopts a qualitative descriptive approach, utilizing observation and literature review as primary data collection techniques. The data sources include teachers, children, and the school principal, ensuring a comprehensive understanding of the implemented strategies. The findings indicate that the integration of play-based learning methods, creative activities, and consistent stimulation significantly contributes to the optimal development of children’s fine motor skills. These approaches not only enhance children’s ability to use coloring tools proficiently but also improve hand-eye coordination and support the development of self-help skills.